IMPLEMENTASI PEMBELAJARAN MENGGUNAKAN GROUP INVESTIGATION DAN PROBLEM SOLVING DENGAN MEDIA VIDEO DALAM MATA KULIAH PKN - Selly Rahmawati (Universitas PGRI Yogyakarta, 2014)
This study aims to determine the implementation learning models of group investigation and problemsolving using video Media in civics courses on multicultural material . Additionally this research also aimed to determine student learning outcomes civics after applied learning model group investigation and problem solving by using video media courses on multicultural material. The method used in this study is in accordance with the design of lesson study. Data collection techniques with tests and questionnaires. Data collection instruments by using LKM and questionnaires. Analysis of the data used is descriptive qualitative and quantitative descriptive. The results of this study were ( 1 ) the implementation learningmodel of group investigation and problem solving using video media is attract the attention of students , making students active , working together , dare to express opinions and understand the material that being taught. ( 2 ) Results of student learning as applied learning model group investigation and problem solving using video media on multicultural material that looks very good on average each cycle has reached the KKM , completeness percentage of students also were above 80 % in each cycle and the percentage affective value of multicultural students also is above 70 % .